Damage detection assessment in reinforced concrete slabs using impact tests. (2017) - Pimentel, Roberto; Guedes, Tulio; Melo, Lucas; Ferreira, Gabriel; Gonçalves, Márcio
Abstract: Use of impact tests to detect damage in reinforced concrete slabs is a less explored technique. This is the subject of this paper, and a cast in place reinforced concrete slab is evaluated, being based on experimental work. To do that, a simply supported slab was built in laboratory and crack-induced damage was achieved by applying static loads in three stages, the last one being close to the ultimate load. After each load stage and removal of the load apparatus, modal tests using an impact hammer were carried out, in order to evaluate the level of changes of the fundamental frequency along the decay after impacting the slab. Plots indicating the variation of the fundamental frequency versus the number of cycles of free decay were obtained. It was observed that the gradient of the time-frequency curves throughout the decay varied according to the level of cracking induced by the application of the static load. This same behaviour was previously reported in the literature from tests in beams, although some differences were observed. In a step further, such pattern of changes of the fundamental frequency was related to a frequency-based global damage detection index. The aim in seeking such relationship is to assess the damage severity directly from the impact tests. Similarities and differences with results from previously reported similar tests are also discussed.